Basic heallth libeactivity and physical culture in high school - V. P. Ozerov; K. M. Smyshnov; T. I. Prokopenko (Вестник Северо-Кавказского федерального университета)
The article raises the urgent issue of the correlation and improving the basics of healthy life-styles and physical education among students. A particular emphasis is placed on the role of physical education in the development of psychomotor skills and healthy life-styles among students.